COST, RETURNS AND PROFITABILITY OF MAIZE-BASED PRODUCTION AMONG MEMBERS OF COOPERATIVE RURAL FARMERS IN IBADAN-IBARAPA ZONE OF OYO-STATE, NIGERIA - Ezeude, Nneka Winifred; Adesina, Shittu Kazeem; Adeeko-Bakare, Fatimah Adetutu (FUDMA Journal of Sciences, 2025)
The study examined cost, returns and profitability of maize production among members of cooperative rural farmers in Ibadan-Ibarapa zone of Oyo State, Nigeria. A multi-stage sampling technique was utilized to select a sample size of one hundred and eight (108) respondents through a well structured questionnaire. Both descriptive and inferential statistics were absorbed to analyzed the data. The findings indicated that majority (88.9%) of the maize-based farmers were in their prime and bracket years of vitality and productivity. This result also implied that a significant portion (75.9%) of the respondents were married, with an average of five (5) persons per households. The findings further showed benefit-cost of 1.42, implied that for every ₦1.00 spent by the farmers on maize production, 42kobo was realized as profit, with benefit-cost ratio exceeded 1, this showed that the enterprise is profitable and economical. The study therefore, recommended that maize farm Input such as fertilizer, seeds among others should be made available to farmers timely at a subsidized rate by government at all levels. Timely and adequate training should be given to maize farmers to acquire modern production techniques in order to boost their production. Maize farmers should be educated on how to battle the challenges associated with their production. Both governments and non-governmental agencies should provide credit facilities for the farmers at low or no interest. Farmers should be encouraged to form more cooperative societies in order to pool their resources together to tackle the financial short fall facing them.